The phonology of Landawe language - Hafsah, Wa Ode Sitti; Aso, La; Taembo, Maulid; Suryati, Nurmin (International research journal of management, IT and social sciences, 2018)
This study aims at investigating the phonology of Landawe Language. The data collecting was done by participant speaking and scrutinizing methods. It was analyzed using apportioned methods. Landawe language has 10 vowel sounds, but there are only five sounds proved as vowel phonemes, they are /i, a, e, o, u/. Besides, Landawe language has 18consonant sounds, they are:/b/, /p/, /d/, /t/, /g/, /k/, /?/, /m/, /n/, /s/, /h/, /l/, /r/, /c/ /y/, /j/, /w/, and /?/. Those consonant sounds are proved as the phoneme. Based on the distribution of the consonant, there is not any consonant that places the final position. They just place the initial and the medial of the word, except /?/ and /y/that only place the medial position, and /j/ that only place the initial position. It means that Landawe language is categorized as vocalist language.